Phosphorylation‐dependent regulation of plant chromatin and chromatin‐associated proteins. Issue 19 (10th July 2014) - Bigeard, Jean; Rayapuram, Naganand; Pflieger, Delphine; Hirt, Heribert; Vondriska, Thoms M.; Jensen, Ole N.
<x xml:space="preserve">Abstract</x> In eukaryotes, most of the DNA is located in the nucleus where it is organized with histone proteins in a higher order structure as chromatin. Chromatin and chromatin‐associated proteins contribute to DNA‐related processes such as replication and transcription as well as epigenetic regulation. Protein functions are often regulated by PTMs among which phosphorylation is one of the most abundant PTM. Phosphorylation of proteins affects important properties, such as enzyme activity, protein stability, or subcellular localization. We here describe the main specificities of protein phosphorylation in plants and review the current knowledge on phosphorylation‐dependent regulation of plant chromatin and chromatin‐associated proteins. We also outline some future challenges to further elucidate protein phosphorylation and chromatin regulation.